Case control study of neuroblastoma in west-Germany after the Chernobyl accident - Michaelis, J; Haaf, H G; Zöllner, J; Kaatsch, P; Krummenauer, F; Berthold, F (Klinische Pädiatrie, 1996)
To explore possible causes of a 1988 incidence peak of infant neuroblastoma in west German regions which were contaminated with more than 6000 Bq/m2 Cs137 from the Chernobyl accident. The primary working hypothesis was that parents of the diseased children had been contaminated by an excessive intake of locally produced food, especially mushrooms or deer. Case control study with 1:2 (cases:controls) matching. Data were collected from the children's parents by questionnaires and telephone interviews. Nation-wide study (former FRG) based on the German Childhood Cancer Registry. Cases born in 1988 and reported with a neuroblastoma to the registry until March 1992. Population-based healthy controls, matched for age, sex and residence at time of diagnosis. The working hypothesis could not be confirmed by the study, because the parents of cases tended to eat less locally grown food than the parents of controls (RR = 0.63, 95% CI:0.20-1.97). Possible influence factors which previously have been described to be associated with neuroblastoma incidence could not be confirmed by the study. Parental exposure to herbicides and pesticides was associated with the occurrence of neuroblastoma (RR = 4.2, 95% CI:1.4-12.9). Neuroblastoma stage distribution in the contaminated regions was shifted towards lower stages as compared to the less contaminated regions and previous age cohorts. The study does not show additional evidence that the observed increase in neuroblastoma incidence might have been caused by exposure to fallout from the Chernobyl accident. The observed shift towards lower clinical stages may rather indicate increased diagnostic awareness. The association between neuroblastoma and parental exposure with herbicides and pesticides resulted from an extensive exploratory data analysis and needs to be confirmed in further studies.